Decision Concepts State Administration Post Entry into Law Number 30 Of 2014 Concerning Government Administration - Muslim Haq. M.; Anshori Ilyas (Universitas Islam Negeri Alauddin Makassar, 2022)
After the enactment of Law no. 30 of 2014 Concerning Government Administration, the Concept of State Administrative Decisions has experienced a shift in meaning as intended in Article 1 Paragraph (3) Law no. 5 of 1986 concerning the State Administrative Court was later amended in Law no. 9 of 2004 concerning Amendments to Law no. 5 of 1965 concerning the State Administrative Court and amended for the second time in Law no. 51 of 2009 concerning the Second Amendment to Law Number 5 of 1986 concerning the State Administrative Court. The research method used is normative research or library research. From the results of this study, in general there are two concepts of state administrative decisions, namely: (1). State Administrative Decision in writing, and (2). Unwritten State Administrative Decisions, among others: (1). Government Administration Actions or Factual Actions and (2). State Administrative Decisions in the form of speech.